Medium-sized Business Actors' Perceptions of Taxes and Their Implications for Business Competitiveness in Bima City - Sinta Nurfiani; Rizky Amelia; Khas Sukma Mulya (CV Edujavare Publishing, 2026)
This study aims to examine the perceptions of medium-sized business owners in Bima City toward income tax and to explore the implications of taxation for the sustainability of medium-sized enterprises. This study employed a qualitative descriptive approach to explore the perceptions of medium-sized business owners in Bima City toward income tax and to examine its implications for the sustainability and competitiveness of their businesses through interviews, observations, and documentation. The collected data were analyzed using the Miles and Huberman interactive analysis model, while the trustworthiness of the findings was ensured through credibility, transferability, dependability, and confirmability based on the framework proposed by Lincoln and Guba. Based on the findings, this study concludes that the perceptions of medium-sized business owners toward taxation in Bima City differ according to their level of tax knowledge, with greater tax literacy leading to more positive attitudes toward tax compliance and business responsibility. The findings also indicate that the impact of taxation on business competitiveness is strongly influenced by entrepreneurs' financial capacity, managerial competence, and ability to manage tax obligations effectively. Overall, the study highlights that improving tax literacy, financial management, and tax compliance practices is essential for enhancing the sustainability and competitiveness of medium-sized enterprises in Bima City.